(untitled) (Research, Society and Development, 2024)
Respiratory physiotherapy is a therapeutic specialty that plays a fundamental role in the prevention and treatment of pulmonary complications in an accessible manner that does not require sophisticated resources for its execution. It consists of a set of physical techniques that, together with medical treatment, facilitate the process of gas exchange. The aim of this research was to describe the therapeutic perspectives of Physiotherapy and Pharmacology in asthmatic children and adolescents. An integrative review was conducted, addressing the main pharmacological and physiotherapeutic treatments for asthma attacks, and the results achieved in each study were organized and presented objectively with the aid of descriptive tables. It was possible to observe that combined pharmacological and physiotherapeutic therapies are potentiated, safe, and effective in controlling and maintaining asthma, since physical exercises are directly linked to the balance of oxidant and antioxidant components, and in the normalization of essential segments for the balance and functionality of the systems, as well as presenting positive effects on lung function. However, further studies are needed to correlate these two therapies, with a larger sample, exploring physiotherapy in its entirety, in order to elucidate whether there is a reduction in adverse events, greater and better adherence to treatment, classifying functional limitations according to the International Classification of Functioning, Disability, and Health (ICF), and predictive values of lung function.